Association among obesity, insulin resistance, and depressive symptoms: a mediation analysis - Guoqiang Xiao; Chenghua Lin; Qiaoyu Lan; Zitong Huang; Chumeng Zhou; Jiajia Hu; Ying Cui; Lujie Wang; Borong Zhou (BMC Psychiatry)
Abstract Background The mechanistic role of insulin resistance(IR) between obesity and Depressive Symptoms has long been debated. Objective This study aims to explore the relationship between BMI and Depressive Symptoms to investigate the mediating role of IR in this association. Methods We rigorously selected data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. Multivariate logistic regression analysis, Restricted cubic splines (RCS) and Subgroup analysis were employed to assess the correlation between obesity and Depressive Symptoms. Mediation analysis was conducted to examine the role of IR in the relationship between Overweight/obesity and Depressive Symptoms. Results After strict exclusion, the final analysis included 12,744 participants. Multivariate logistic regression analysis indicated a significant association between obesity and Depressive Symptoms. Subgroup analysis revealed an interaction from lack of exercise and vigorous activity levels to the association between obesity and Depressive Symptoms in the physical activity group (P for interaction < 0.05); A significant interaction was found between BMI and smoking status (P for interaction < 0.05). BMI was found to have an S-shaped association with Depressive Symptoms, becoming positively correlated after reaching a turning point (BMI > 23.22 kg/m², p < 0.001). IR partially mediated the potential impact of overweight/obesity on Depressive Symptoms (IR: 54.13%, p = 0.018). Conclusion Our study confirms a significant association between obesity and Depressive Symptoms. IR partially mediates the association between overweight/obesity and Depressive Symptoms. Furthermore, appropriate physical exercise and smoking may reduce the risk of depressive symptoms.